2020
DOI: 10.1186/s12898-020-00297-4
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal of wild radishes and its association with within-population spatial distribution

Abstract: Background: The wild radishes, Raphanus raphanistrum and R. pugioniformis (Brassicaceae) are native to the East Mediterranean region. However, whereas R. raphanistrum is widely distributed worldwide, the endemic R. pugioniformis is limited to specific habitats. In R. raphanistrum the diaspores of the indehiscent fruits comprise glabrous, light, single-seeded segments, whereas the intact fruits of R. pugioniformis are heavy and covered with spiny backwardpointing trichomes. We aimed to investigate whether the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…pugioniformis, an endemic species of the eastern Mediterranean [6], has received limited research attention. The relationships among these species remain largely unresolved [7]. However, a cDNA sequence analysis conducted on one population from each of eight Raphanus taxa (excluding R. pugioniformis) provided compelling evidence supporting the monophyly of the crop cultivars and the native and weedy forms of R. r. raphanistrum [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pugioniformis, an endemic species of the eastern Mediterranean [6], has received limited research attention. The relationships among these species remain largely unresolved [7]. However, a cDNA sequence analysis conducted on one population from each of eight Raphanus taxa (excluding R. pugioniformis) provided compelling evidence supporting the monophyly of the crop cultivars and the native and weedy forms of R. r. raphanistrum [2].…”
Section: Introductionmentioning
confidence: 99%
“…Weedy R. r. raphanistrum is frequently found as a troublesome invader in small grain fields and is widely recognized as one of the most significant agricultural weeds globally [7][8][9]. Weedy radish has been extensively utilized in ecological and evolutionary research, specifically for investigating plant-insect interactions [10][11][12][13][14][15][16], and possesses valuable genomic resources that render it an ideal system for studying the origins and adaptations of agricultural weeds, enabling researchers to address pertinent questions in this field [17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, its close relative, Raphanus pugioniformis DC. ( Rp ) is endemic to northern Israel, southern Lebanon, and Syria, growing on Terra Rossa and basaltic soil ( Ziffer-Berger et al., 2020 ). This species is not studied as well as Rr due to its lower distribution range and not interfering with agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…R. raphanistrum occurs mainly on sandy soils of coastal plains (=Calcisol), while R. pugioniformis is restricted to mountainous areas in north-eastern Israel on Terra Rossa (=Luvisol) and basaltic (=Vertisol) soils. (B) R. raphanistrum scattered worldwide (pale blue areas on the world map; ( Holm et al., 1997 )) from its native distribution area of the Mediterranean basin (highlighted by dark blue; ( Ziffer-Berger et al., 2020 )). R. pugioniformis is restricted to northern Israel, southern Lebanon, and Syria.…”
Section: Introductionmentioning
confidence: 99%
“…Weedy radish belongs to the family Brassicaceae genus Raphanus and is a native population in the Mediterranean region (Conner et al 2011;Al-Shehbaz 2012;Conner et al 2014;Klinger et al 1991). Raphanus sativus comprise four major types including two fruit crops (Oilseed and edible pod Rat-tail) and two root crops (European radish and Asian daikon) but the relationships among these species are not well known (Ziffer-Berger et al 2020). According to the Campbell et al, (2006) cDNA sequence of Raphanus taxa revealed monophyly of native and weedy R. raphanistrum.…”
Section: Introductionmentioning
confidence: 99%